The nation city : why mayors are now running the world - Emanuel, Rahm, 1959- (Alfred A. Knopf, 2020)
"At a time of anxiety about the effectiveness of our national government, Rahm Emanuel provides a clear vision, for both progressives and centrists, of how to get things done in America today--a bracing, optimistic vision of America's future from one of our most experienced and original political minds"--